Advantages of quality protein maize use in broiler diets - Dragana Ignjatović-Micić; Jelena Vančetović; Ksenija Marković; Danijela Ristić; Jovan Pavlov; Zoran Čamdžija; Marija Kostadinović (Scientia Agricola)
ABSTRACT: Meat consumption has been declining in favor of a shift towards poultry due to its lower price, health benefits and consumers’ preference. One of the ways to enhance broiler production and quality is to substitute standard maize (SM) with quality protein maize (QPM) in animal diets. QPM is a high lysine maize with improved nutritional and biological values, developed by the selection of a naturally occurring recessive opaque2 mutation, which can reduce the use of costly feed components - synthetic lysine and protein ingredients such as soybean and fishmeal. Different feeding trials with QPM in broiler diets indicated that body weight gain (BWG), feed conversion ratio (FCR), breast meat yield (BMY), and abdominal fat (AF) are the main improved features. Herein, an overview of the effects of QPM on broiler performance and carcass characteristics, as well as the financial effects of its use, is presented. Different effects of QPM were observed, depending, in the main, on the QPM hybrid used in the trial. The possible reasons for the discrepancies and suggestions for overcoming them, focused on the utilization of the full potential of QPM, are discussed.